ARCHAEOLOGY AND EPIC: BUTRINT AND UGOLINO VERINO'S CARLIAS. (2nd October 2014) - Gwynne, Paul; Hodges, Richard; Vroom, Joanita
Abstract : The Epirote port of Butrint (now in Albania) features significantly in the neo-Latin epic, the Carlias, by the Florentine Ugolino Verino (1438–1516). This poem was recast on the occasion of the invasion of Italy by Charles VIII of France, to encourage the young king to imitate his ancestor, Charlemagne, and undertake a crusade. This essay focuses upon the poetic description of Butrint in the light of recent excavations. It reconstructs the run-down character of this fortified Venetian town, as well as the material living conditions of its occupants in 1493. The essay considers how Verino's narrative was shaped by literary sources, rather than the actual circumstances of the port. Abstract : Il porto epirota di Butrint (oggigiorno in Albania) compare nell'epica neolatina, il Carlias del fiorentino Ugolino Verino (1438–1516). Questo poema fu rimaneggiato in occasione dell'invasione dell'Italia ad opera di Carlo VIII di Francia, per incoraggiare il giovane re ad intraprendere una crociata, imitando il suo antenato Carlo Magno. Questo saggio si concentra sulla descrizione poetica di Butrint alla luce dei recenti scavi. Ricostruisce la fatiscente città fortificata veneziana unitamente alle condizioni della vita quotidiana dei suoi occupanti nel 1493. L'articolo prende in considerazione come il racconto di Verino fu plasmato sulle fonti letterarie piuttosto che grazie alle effettive condizioni del porto.